FIGURE 12. Gilbertaster caribaea A in New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer - Mah, Christopher L. (Zenodo, 2020)
FIGURE 12. Gilbertaster caribaea A. Feeding on the primnoid octocoral Plumarella sp.Richardson Ridge, Gulf of Mexico, 797 m. B. USNM 1580844 feeding. Richardson's Jellyfish, 592 m, C. Central Plateau Scarp, off SE coast of United States. 886 m, D. Richardson Ridge, Gulf of Mexico, 781 m E. Purple amphipods on oral surface in tube foot grooves (indicated by arrows). Central Plateau Scarp, Off SE coast of United States, 901 m. : Published as part of Mah, Christopher L., 2020, New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer, pp. 201-260 in Zootaxa 4766 (2) on page 229, DOI: 10.11646/zootaxa.4766.2.1, http://zenodo.org/record/3764018